KONSEP KAFIR PERSPEKTIF QURAISH SHIHAB DAN IMPLIKASINYA DENGAN KONTEKS KEINDONESIAAN - Zayyadi, Ach.; Najiburrahman, Najiburrahman; Khaer, Abu; Wilandari, Wilandari (Risâlah, Jurnal Pendidikan dan Studi Islam, 2022)
The term "infidel" by non-Muslim groups to incite discriminatory sentiments is a contemporary societal problem. Unbelievers and their levels have already been treated in the Qur'an. Thus, a more appropriate method is required to comprehend the term thoroughly. This method employs a qualitative paradigm, in which the researcher attempts to investigate several factors (1). The word "infidel" has many meanings (2). The ramifications in the context of Indonesia. Based on the Rules or Method of Tafsir agreed upon by the scholars and incorporated in Quraish Shihab's Tafsir Al-misbah, this article seeks to restore the word infidel. The findings show that non-Muslims understand the word infidel in Tafsir Al-Misbah in a variety of ways, including (1) not believing in the genuine religion (2) distrusting the prophet (3) denying God's benefits (4) leaving religious guidance even if you have faith (5) breaking away, and so on.